SYNTHESIS OF ZSM-5 FOR CATALYTIC USE, AND CHARACTERIZATION BY DRX AND FTIR - Delmás R., D. (2009)
Due to the importance that has the ZSM-5 zeolitic catalyst in the acid form or in the modified form with transition metals by it’s application in catalytic alkylation, transalkylation, isomerization and polymerization reactions of aromatic compounds and by it’s characteristic properties, like as: a great surface area, adsorption capacity, structure that permit the active sites creation and one excellent form selectivity. In the present investigation it’s show the synthesis of NaZSM-5 zeolite with atomic relation (Si/Al) = 140 , the preparation of HZSM-5 catalyst by ionic interchange method. Moreover, it’s show the characterization of the synthesized zeolites by FTIR and by XRD. So, the FTIR band spectrums of Na ZSM-5 and HZSM-5 dried and calcined, respectively, show the peculiars bands to the characteristics vibrations presents in the ZSM-5 zeolites. Finally, the XRD results show the crystal structures of the NaZSM-5 and HZSM-5 zeolites.